Consequence analysis of catastrophic release of diesel and fuel oil from their storage tanks using SCIA software - Mustapha, S.; El-Harbawi, M. (SCIENCEDOMAIN international (SDI), 2016)
Catastrophic release of diesel and fuel oil from their storage tanks can lead disasters to human, property and the environment. Thus consequences analysis of the accident has significant importance to human communities living in the surrounding area and the authorities involved in land planning. Consequence analysis is normally carried out using mathematical models for predicting the impacts of chemical accidents. This paper presents result of the consequence analysis from study cases namely catastrophic release of diesel and fuel oil from their storage tanks using Simulation of Chemical Industrial Accident (SCIA) software. The software is a user-friendly and effective tool for evaluating the consequences of major chemical accidents, process decision making for land-use planning, namely locating suitable hazardous installations, hazardous waste disposal areas and emergency response plan. Release of diesel and fuel oil might escalate to pool fires and thus require evaluating their characteristics and the posed hazard. It is recommended for future land planning and development, a town must be located at least half kilometre away from the storage tanks to minimize the disaster impacts.